The Concept of Honesty in Javanese People's Perspective - Lestari, Sri; Adiyanti, M.G. (Faculty of Psychology, Universitas Surabaya, 2012)
The aim of this study was to find out the concept of honesty in Javanese perspective. Parti- cipants were four Javanese families consisting father, mother, and the first-born adolescent child. The themes that emerges from participants’ indepth interview were the meaning of honesty, indicators of honesty, and motives that encourage to be honest. The findings indicate that the Javanese concept of honesty is universal, but the acceptance of dishonesty was influenced by relational aspects. Implications of this results to education setting are discussed. Penelitian ini bertujuan mengeksplorasi konsep jujur dalam perspektif orang Jawa. Partisipan penelitian ini adalah empat keluarga Jawa yang terdiri atas ayah, ibu, dan anak remaja sulung. Dari wawancara mendalam terhadap 12 orang partisipan diperoleh tema tentang makna jujur, indikasi jujur, dan motif-motif yang mendorong untuk berperilaku jujur. Temuan eksplorasi mengindikasikan bahwa konsep jujur dalam perspektif orang Jawa bersifat universal, namun penerimaan terhadap ketidakjujuran dipengaruhi unsur relasional. Selanjutnya didiskusikan implikasi hasil penelitian pada dunia pendidikan.